The Experience of Fertility Preservation in a Single Tertiary Center in Korea - Choi, Yae Ji; Hong, Yeon Hee; Kim, Seongbeen; Kim, Seul Ki; Lee, Jung Ryeol; Suh, Chang Suk (Frontiers in Endocrinology, 2022)
Objective Oocyte (OC), embryo (EC), and ovarian tissue cryopreservation (OTC) are options for fertility preservation (FP) before going through gonadotoxic cancer treatment, or anticipated fertility decline in benign ovarian diseases, or for planned OC. The aim of this study is to report outcomes of FP in a single tertiary hospital in Korea. Methods This is a retrospective study of OC, EC, and OTC cycles. All patients who visited or were referred to the infertility clinic at the Department of Obstetrics and Gynecology for the purpose of FP between 2010 and October 2021 were included. Results A total of 564 controlled ovarian stimulation cycles were conducted in 416 women. Three hundred fifty-seven women underwent 494 OC cycles. Most patients were diagnosed with breast cancer (22.4%), followed by endometriomas (21.9%), and then by planned OC (20.7%). Cases of OC have increased over the years, peaking at 109 cycles in 2019 compared to one in 2010. Fifty-nine women underwent 70 EC cycles, and breast cancer (50.8%) was the most common indication. Repetitive OC and EC cycles were undergone in 92 and 9 women, respectively (mean number of repetition, 1.37 and 1.19 times in OC and EC, respectively), yielding a maximum number of 33 oocytes or 23 embryos being cryopreserved per patient. The utilization rate was 3.1% (11/357) in OC and 16.9% (10/59) in EC. Twenty-six women underwent OTC, and gynecologic cancer was the most common indication (9/26, 34.6%). One woman had the cryopreserved ovarian tissue retransplanted and successfully generated embryos. Conclusion OC, EC, and OTC are possible options for preserving fertility, and these opportunities should be provided for women at risk of fertility decline or those who are eager to protect their future fertility. This is the first report on long-term FP outcomes in a single tertiary center in Korea. We expect that there will be more cases over the years and more women returning to use their gametes or embryos for pregnancy.